Online and Offline Reading Materials from Students’ Perspective - Diska Fatima Virgiyanti; Aries Fachriza; Eka Indah Nuraini; Dinar Dipta; Latifa Annisa Hafiz (SAGA: Journal of English Language Teaching and Applied Linguistics, 2024)
In this digital era, reading can be done anywhere and anytime. Nowadays, as the rapid development of technology, there are many learning sources available in online platform such as website. As a result, it also affected students’ habit in reading. Moreover, reading online is different from reading offline. In reading offline, the students need printed reading materials such as book, novel, newspaper, or magazine. However, offline reading does not need any printed materials, except the computer, laptop, or smart phone. Students often got difficulties in choosing their reading materials when they are given freedom to choose their own materials from online or offline sources. In this article, the researcher aimed to find out the students’ perspective toward reading using online and offline materials as well as its benefits and drawbacks. This research used descriptive qualitative research method. The researcher obtained the data from questionnaire, interview, and field observation. There were 25 students involved in this research. The findings indicated that students usually read in their free time, they are familiar with e-book materials, students’ reading motivation affected by formal features of a book, printed book is easier to be understood, both online and offline materials is interesting, online platform is more update in giving news, and they like to read book from both Indonesian and foreign authors.